Sử dụng một số phần mềm công nghệ số trong dạy học “Luyện tập về danh từ” - môn Tiếng Việt cho học sinh lớp 4 - Nguyễn Thị Thu Tính, Nguyễn Thị Thu Tính; Nguyễn Thị Dung, Nguyễn Thị Dung; Phạm Mai Phương, Phạm Mai Phương (Tạp chí Giáo dục, 2024)
Using some digital technology software in teaching is currently receiving attention and increasing attention, helping students develop the qualities, abilities and skills necessary for learning, while making the lessons more lively and not boring. Applying software in teaching helps students to be interested and actively participate in learning activities. Each software has different outstanding features; depending on the goals of each teaching activity, we can choose the appropriate software. The article analyzes the use of some digital technology software in teaching “Practice in nouns” in Vietnamese for 4th graders and illustrates the application of software: Blooket, Padlet, Quizizz.... This is one of the software that can be applied to contribute to improving the interest and effectiveness of lessons, suitable for the goals and content of the lesson on nouns for 4th graders.